# Find The Derivative of the Function x^2√(1-x^2)

• Nov 10th 2011, 05:28 PM
Deo3560
Find The Derivative of the Function x^2√(1-x^2)
f(x)=(x^2)(√(1-x^2))

f'(x)=(2x)(√(1-x^2))+(x^2)(1/2)(√(1-x^2))^-1)(-2x)

f'(x)=(2x)((1-x^2)^1/2)+(x^2)(1/2)(√(1-x^2)^-1)(-2x)

f'(x)=√(4x^2-4x^4)+(1/2)(-2x^3)(1/(√(1-x^2))

umm i'm lost, i probably didn't even get the above right (sorry the format sucks pretty bad)

http://mathway.com/math_image.aspx?p...MB03?p=66?p=22

never mind i found a picture
• Nov 10th 2011, 05:47 PM
Quacky
Re: Find The Derivative of the Function x^2√(1-x^2)

$x^2\sqrt{1-x^2}$

I'd use the product rule.

Let $u=x^2$

then $\frac{du}{dx}=?$

Let $v=(1-x^2)^{\frac{1}{2}}$

then $\frac{dv}{dx}=?$

You should be able to proceed from here.
• Nov 11th 2011, 01:05 AM
sbhatnagar
Re: Find The Derivative of the Function x^2√(1-x^2)
$x^2\sqrt{1-x^2}=\sqrt{x^4-x^6}$

and

$\frac{d}{dx}(\sqrt{f(x)})=\frac{f'(x)}{2\sqrt{f(x) }}$
• Nov 11th 2011, 05:19 AM
CaptainBlack
Re: Find The Derivative of the Function x^2√(1-x^2)
Quote:

Originally Posted by Deo3560
f(x)=(x^2)(√(1-x^2))

f'(x)=(2x)(√(1-x^2))+(x^2)(1/2)(√(1-x^2))^-1)(-2x)

f'(x)=(2x)((1-x^2)^1/2)+(x^2)(1/2)(√(1-x^2)^-1)(-2x)

$f'(x)=(2x)(1-x^2)^{1/2}-(x^2)(1/2)(1-x^2)^{-1/2}(-2x)$

It is right up to here, and may be simplified:

$f'(x)=(2x)(1-x^2)^{1/2}+\frac{x^3}{(1-x^2)^{1/2}}$

It is easier to proceed by taking out a factor of $x \sqrt{1-x^2)$

$f'(x) =x(1-x^2)^{1/2}\left[2 -\frac{x^2}{1-x^2} \right]$

That square bracket may be simplified further if you wish.

CB